A moulage aplicada no vestuário jeanswear - Messias, Juliana Aparecida de (2014)
This research seeks to develop garments for jeanswear segment using moulage as a creative tool to reach more elaborated structures and articulate elements and details that enrich the models during product confection. Therefore, a review of literature on the emerging of moulage and its importance as applied by big names in the fashion that their creations technique was performed. In addition, we developed a history on the trajectory of jeans, with its main aspects textile raw material for making clothes and its representation as an icon in mass culture. The study further characterized as a qualitative approach to conducting a field survey that investigated the potential needs of the public chosen target market that later would help on developing the design of the collection.